2021
DOI: 10.12688/hrbopenres.13303.2
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Public Involvement (PPI) in preclinical research: A scoping review protocol

Abstract: Introduction: Patient and public involvement (PPI) aims to improve the quality, relevance, and appropriateness of research and ensure that it meets the needs and expectations of those affected by particular conditions to the greatest possible degree. The evidence base for the positive impact of PPI on clinical research continues to grow, but the role of PPI in preclinical research (an umbrella term encompassing ‘basic’, ‘fundamental’, ‘translational’ or ‘lab-based’ research) remains limited. As funding bodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Two reviewers P. C. and M. F. conducted data extraction using a data extraction form developed in accordance with the JBI guidelines 14 and the study protocol. 12 The following information was extracted for each included study: author(s); year; title; country of origin; the scientific discipline/context of the study; who took part in the PPI component (PPI Contributors); the reason for conducting PPI (PPI Rationale); what researchers sought to accomplish with PPI (Aims of PPI); which PPI approach was used (PPI Format); how PPI was implemented (PPI Methods); stages of implementation according to NIHR 1 ; benefits associated with PPI; challenges associated with PPI; impact of PPI on study; if/how PPI was evaluated; elements with potential application within our preclinical PPI project. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two reviewers P. C. and M. F. conducted data extraction using a data extraction form developed in accordance with the JBI guidelines 14 and the study protocol. 12 The following information was extracted for each included study: author(s); year; title; country of origin; the scientific discipline/context of the study; who took part in the PPI component (PPI Contributors); the reason for conducting PPI (PPI Rationale); what researchers sought to accomplish with PPI (Aims of PPI); which PPI approach was used (PPI Format); how PPI was implemented (PPI Methods); stages of implementation according to NIHR 1 ; benefits associated with PPI; challenges associated with PPI; impact of PPI on study; if/how PPI was evaluated; elements with potential application within our preclinical PPI project. …”
Section: Methodsmentioning
confidence: 99%
“…Three members of the PPI Advisory Panel are PPI contributors and were involved in the project from the beginning, including project planning and protocol development stages. 12 Completed data extraction forms were circulated to PPI Advisory Panel members in advance of a scheduled meeting. The extracted data were discussed in terms of themes/trends identified by the patient partners and other panel members, aspects relevant to the spinal cord repair project, and aspects relevant to preclinical PPI more generally.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinicians emphasised that it would be important to clearly communicate the preliminary nature of research findings, as they believed people with SCI might develop high expectations for a cure from early research findings. This contrasts with views expressed by people with SCI, who reported that being involved in PPI could have the opposite effect, that learning more about research would reduce their hope for a cure 24 . The importance of developing strong relationships noted by study participants is generally accepted to be essential for successful PPI but can be challenging to achieve 23, 25 , and has formed the basis of a model for PPI in SCI 13 .…”
Section: Discussionmentioning
confidence: 63%